Pembuatan Komposit Serat Campuran Tandan Kosong Sawit (TKS)/E-Glass Matriks Epoxy Dengan Metode Hand Lay-Up - Rivo Fernando; Warman Fatra; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Empty Fruit Bunch (EFB) is one of the palm oil plantation waste that has not been utilized optimally. EFB fiber has a good strength, low density, and it can be used for substituting synthetic fiber composite. However, the strength of EFB fibers is lower than that of synthetic fibers. In addition, EFB fibers also have a poor interface with the matrix and relatively high water absorption. Several methods can be used to increase the bonding strength between the fibers and matrix, alkaline treatment and the addition of coupling agent into the matrix. One of the coupling agent is Maleated Natural Rubber (MNR). The objective of this research is to investigate the effect of the ratio of EFB /E-Glass fibers, ratio of hybrid fibers and matrix as well as the addition of MNR on tensile strength, flexural strength and water absorption of EFB/E-Glass epoxy hybrid composite. The highest tensile strength (77.254 MPa) was obtained in the composition of 40% EFB fiber, 60% matrix and 9% MNR. The highest flexural strength (147.446 MPa) was obtained in the composition of 33.18% EFB fiber, 50% matrix and 10% MNR. The lowest water absorption (4.46%) was obtained in the composition of 40% EFB fiber, 40% matrix and 11% MNR. The results show that the tensile strength increases with the addition of EGlass. While the addition of the matrix and MNR does not significantly affect tensile strength. Flexural strength increases with increasing number of E-Glass and matrix. Keywords: Empty Fruit Bunch (EFB); Hybrid Reinforce; Alkaline Treatment; coupling agent; Maleated Natural Rubber (MNR)